O componente físico-natural água na geografia escolar em Anápolis/GO - Zózimo, Marco Aurélio Dias (2022)
Water is considered one of society's most important resources. Its uses go through different uses. Its association with the teaching of Geography is proposed as one of the physical-natural components of the geographic space. This theme is worked from different perspectives in the geographic space and, therefore, one of the questions we have is how to teach it in a meaningful way to the students and, at the same time, enable them to undertake the reality from a geographic perspective? As one of the indications presented in the literature is to mobilize the students' daily life to guide the teaching and learning process in Basic Education, we also wonder: how to mobilize this daily life when working with issues related to water? And also, what issues have been addressed when dealing with this component in Basic Education? Thus, having water as an object of study, we aimed to understand the knowledge mobilized by Geography teachers when working with the topic of water in the Final Years of Elementary School in the State Education Network (REE) in Anápolis/GO. And as specific objectives: to verify how the topic of water has been investigated in School Geography; to identify themes and analyze the concepts used by Geography teachers when teaching classes related to the water component in the Final Years of Elementary School; to understand the themes and conceptions related to water in teaching materials (textbooks and curricula) used by Geography teachers participating in the research; to propose, in partnership with the investigated teachers, conceptual systems for the work with water components in School Geography. Taking into account the assumptions of qualitative research, we established as spatial cutout a School of the State Education Network of the city of Anápolis, and as research subjects, the Geography teachers of the Final Years of Elementary School. We performed different procedures, such as: literature review, mobilization of questionnaires to the teachers participating in the research, analysis of curriculum documents (textbooks, BNCC and DC-GO) and workshops. In addition, we also conducted surveys through the state of knowledge (1972 to 2019) in dissertations and theses defended in Graduate Programs in Geography, approved by the Coordination for the Improvement of Higher Education Personnel (CAPES), which deal with the topic of water. Finally, we start from discussions that seek to articulate the theoretical and methodological relevance of initial training in the development of teaching practice. This took place through the aforementioned procedures. In these discussions, the teachers presented the existence of gaps between what is taught in schools through the contents related to the natural-physical components, especially water, and the contents learned in their initial training. Thus, we highlight the relevance of concept formation when developing reflections between everyday and scientific concepts. Therefore, this work required the methodological guidelines proposed by Vygotsky (1998), under the fundamental relationship between pedagogical mediation and concept formation, from the teaching and learning process, based on the students' daily lives.